The Influence of Work Motivation And Loyalty on Employees Work Ethos Pt. United Rope Medan - Steven Chandra; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin (Institute of Computer Science (IOCS), 2022)
Work ethic is important as the totality of the employee's personality and the way employees express, perceive, believe and give meaning to something that encourages them to act in achieving optimal work results. Motivation is a set of forces that come from within and from outside a person who encourages him to work better and is willing to spend a higher level of effort to achieve the direction and goals that the company wants to achieve. Loyalty is the nature of an employee who is willing to participate in achieving company goals with all his abilities, skills, thoughts and time and keeps company secrets and does not take actions that harm the company as long as the employee is still active in the company. Regression analysis used in this study is multiple linear regression. The sampling technique used is a saturated sample of 73 employees. The scale used is a Likert scale. Simultaneously there is a significant influence between the variables of motivation and work loyalty on the work ethic of employees of PT. United Rope. While partially found the motivation variable has a significant effect on the work ethic of employees of PT. United Rope. Partially, it was found that the work loyalty variable had a significant effect on the work ethic of the employees of PT. United Rope.